2000
DOI: 10.1046/j.1365-2346.2000.00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Does etomidate increase postoperative nausea? A double-blind controlled comparison of etomidate in lipid emulsion with propofol for balanced anaesthesia

Abstract: In a double-blind randomized study, the incidence and severity of postoperative nausea and vomiting was investigated with a new formulation of etomidate (Etomidate-(R)Lipuro, B. Braun Melsungen AG, Germany) compared with propofol for induction of a balanced anaesthesia with isoflurane/fentanyl in air. The incidence and intensity of nausea was examined by use of a visual analogue scale (VAS; 0-100 mm) at 1, 2, between 6 and 8, and 24 h postoperatively. One-hundred-and-sixty-four patients undergoing orthopedic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Early investigators reported that post-operative nausea and vomiting incidence after induction with etomidate is around 40%, 50,55 comparable to that following barbiturates, 43,56 and higher than that following propofol. 63 More recently, the incidence of nausea after induction with etomidate in lipid emulsion was reported to be similar to that associated with propofol, 64,65 while the incidence of vomiting was higher with etomidate. 65 …”
Section: Clinical Pharmacologymentioning
confidence: 92%
See 1 more Smart Citation
“…Early investigators reported that post-operative nausea and vomiting incidence after induction with etomidate is around 40%, 50,55 comparable to that following barbiturates, 43,56 and higher than that following propofol. 63 More recently, the incidence of nausea after induction with etomidate in lipid emulsion was reported to be similar to that associated with propofol, 64,65 while the incidence of vomiting was higher with etomidate. 65 …”
Section: Clinical Pharmacologymentioning
confidence: 92%
“…63 More recently, the incidence of nausea after induction with etomidate in lipid emulsion was reported to be similar to that associated with propofol, 64,65 while the incidence of vomiting was higher with etomidate. 65 …”
Section: Clinical Pharmacologymentioning
confidence: 92%
“…Etomidate is a hydrophobic compound associated with pain on injection but this effect has been reduced by formulation in a lipid emulsion. Myoclonic movements, trismus and post-operative nausea and vomiting are said to be more frequent with etomidate [20-23]. The main concern, however, has been the inhibition of steroid synthesis produced by etomidate.…”
Section: Con: Etomidate Is Not Safe In Hemodynamically Unstable Critimentioning
confidence: 99%
“…A variety of antiemetics acting via different mechanisms are used for prevention and treatment of PONV. In general, clinicians choose among these agents based upon side effect profile, personal experience, cost, and formulary considera-tions (20)(21)(22). Previous study suggested that commonly used antiemetics reduce the risk of PONV by approximately 25 percent (23).…”
Section: Discussionmentioning
confidence: 99%